A feasibility study of methane reforming by partial oxidation. - Zhu, Jian N. (Curtin University, 2001)
Utilisation of natural gas (mainly methane, CH[subscript]4), a clean and abundant resource, is of great importance. Conventional method, steam reforming, though still dominant, requires a considerately high capital investment and an intensive energy input. Reforming natural gas by partial oxidation, potentially one of the most attractive alternatives, has been investigated vigorously for decades, mainly focusing on looking for suitable catalyst and understanding of the mechanisms of methane partial oxidation. This work focuses on the feasibility of methane partial oxidation reforming from gas phase reaction under fuel-rich conditions.Firstly, a detailed thermodynamic analysis has been conducted, which covers a broad range of operation conditions of temperature up to 2073 K, pressure up to 100 atm and initial O(subscript)2/CH(subscript)4 ratio of 0 to 2.5. It has been found that high syn-gas (H(subscript)2 and CO) yields can be achieved when the temperature is above 1073 K and the initial O(subscript)2/CH(subscript)4 ratio close to 0.5. High pressure is not favoured. However, high temperatures can suppress the effect of high pressures.Carbon deposition, a crucially important factor in methane partial oxidation, is mainly examined by means of thermodynamic analysis. Solid carbon was identified the major carbon deposition form, which could severely happen if the initial O(subscript)2/CH(subscript)4 ratio is less than 0.5. This feature was also indirectly proven during the experimental tests.Secondly, a series of CHEMKIN simulations were performed using various CH(subscript)4 oxidation reaction mechanisms. The general trend of the CH(subscript)4 partial oxidation reforming was revealed by simulations using the GRI, NIST and Konnov mechanisms. A new concept characterising CH(subscript)4 partial oxidation was conceived. i.e., a fast oxidation zone and a slow conversion zone, the reaction is under chemical control that requests high operating temperatures, and the reaction can be accelerated by using relatively high initial 0(subscript)2/CH(subscript)4 ratios.Experimental tests were performed to verify the findings obtained in thermodynamic and kinetic studies, and to identify appropriate reaction schemes for further analysis. Prediction from the NIST mechanisms has shown to be in good agreement with experimental observation when the temperature is less than 1273 K. For higher temperatures the NIST under-predicts the H(subscript)2 yield caused by the lack of carbon formation mechanisms. Two other mechanisms (Konnov and GRI) predicted similar trends but the reaction predicted commenced earlier. Therefore, the NIST was identified to be the best.NO(subscript)x catalytic effect on CH4 oxidation at fuel-rich conditions was confirmed experimentally. However, this effect only exists where the oxygen is available. Therefore, employing NO(subscript)x cannot help the CH(subscript)4 partial oxidation in the second reaction zone. Solely relying on NO(subscript)x to speed up the process or lower the operating temperature is not possible. However, employing NO(subscript)x to initiate the reaction at lower temperatures is viable. The possibility of taking the advantage of NOx catalytic effect for direct synthesis of CH3OH (methanol) has been shown feasible and, more attractively, the operating temperatures required are much lower than that for syn-gas production.Among three reaction schemes, i.e., the Glarborg, Bromly and Dagaut, which are able to account for the NO(subscript)x catalytic effect, the Glarborg mechanism proved to be the best in reproducing experimental measurements for syn-gas production tests. However, none available mechanisms can predict similar magnitude of the direct synthesis of CH(subscript)3OH. To understand the mechanisms of NO(subscript)x catalytic effect, a reaction scheme, Partial Oxidation Mechanisms (POM), has been composed successfully adding five additional reactions into the NIST. The POM can reveal the major catalytic reaction pathways and it is suitable for CH(subscript)4 partial oxidations both with and without NO(subscript)x addition.Finally, a series of simulations were conducted to conservatively estimate the feasibility of CH(subscript)4 partial oxidation using POM. High syn-gas yield is achievable within a reasonable residence time using adiabatic reactor. The variables significantly affecting the syn-gas yield, are preheating temperature, operating pressure, inert dilution, initial ratio of O(subscript)2/CH(subscript)4 and residence time. If NO(subscript)x is used as a catalyst, the preheating temperature can be further reduced.